-7/33=m+1/3

Simple and best practice solution for -7/33=m+1/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7/33=m+1/3 equation:


m in (-oo:+oo)

-7/33 = m+1/3 // - m+1/3

-m-7/33-(1/3) = 0

-m-7/33-1/3 = 0

-m-6/11 = 0 // + 6/11

-m = 6/11 // * -1

m = -6/11

m = -6/11

See similar equations:

| b-7=-15 | | d+2=26/9 | | -30/7=n-2/7 | | a-1/4=-11/12 | | 9/10+a=9/10 | | 7t=-35 | | 3d=1/4 | | k+2/5=52/55 | | a+5=29/7 | | x+4/9=-14/9 | | a-1/8=-67/88 | | 6x-10=10-4x | | 2x=-2/7 | | -1/18=m-5/9 | | -2/3+w=1/3 | | b/5=-3 | | k+3/7=85/84 | | a/-7=-6 | | k/-4=6 | | 31/9=k+4/9 | | b-3=-32/9 | | t-3/8=53/8 | | -6m=5/2 | | d-7/8=9/8 | | t+6=12 | | d-5=-14/3 | | -5/7=t-1 | | x-3/4=-27/4 | | d-1=-1/6 | | m-7/9=-1/36 | | k-2/7=-11/14 | | 3/10+b=7/10 |

Equations solver categories